“Siberian Possibilities”: German Reception of Dostoevsky - Nataliya A. Kopcha (Studia Litterarum)
At the beginning of the 20 th century, in Germany that was going through a period of cultural pessimism and crisis of conservative values, a new political dimension eloped in the German reception of Dostoyevsky. Arthur Moeller van den Bruck, essayist and future ideologist of Conservative revolution, the author of the book Third Reich developed such approach. From 1906 through 1919, he published the first complete works of the Russian writer in German that influenced further adaptation of Dostoyevsky. The aim of this article is to analyze the perception of Siberia in the prefaces written by Moeller with no other purpose but to declare new conservative views. The analyzed sources are devoted to a subject of Siberia which is considered by Moeller in different political and socio-philosophical categories. The author comes to a conclusion that Moeller sees Siberia (1) as a place where Dostoyevsky had changed his views and had discovered the “true” Russian people; (2) as a territory whose population had revolutionary moods coming not “from the doctrine” but “from the instinct”; (3) as a place with opportunities for German-Russian future union capable to overcome Western rationalism. Thus Moeller enters the multilateral political myth concerning not only the essence Siberia of but also the future of Germany.